Novel Technique for Descemetorhexis Under Ophthalmic Viscosurgical Devices and Air. Issue 9 (September 2021) - Coco, Giulia; Pagano, Luca; Borgia, Alfredo; Kaye, Stephen B.; Romano, Vito
Abstract : Purpose: The aim of this study was to describe a novel technique for descemetorhexis that combines the advantages of stable anterior chamber (AC) associated with ophthalmic viscosurgical devices and optimal surgical visualization seen with air to overcome the issues of poor Descemet membrane (DM) visibility or AC instability when each is used alone. Methods: This study is a description of a new surgical approach. Results: We describe a new technique for performing descemetorhexis. The simultaneous presence of cohesive ophthalmic viscosurgical device and air in the AC offers optimal DM visualization and guarantees a stable AC during this surgical step. It does not require an additional incision for an AC maintainer. Conclusions: The described technique may facilitate the surgical step of descemetorhexis, offering improved AC stability and better visualization of the DM. It may reduce early postoperative graft detachment due to the presence of residues of the recipient's diseased DM. Abstract : Supplemental Digital Content is Available in the Text.